2021
DOI: 10.1364/ome.419975
|View full text |Cite
|
Sign up to set email alerts
|

Near-perfect absorber consisted of a vertical array of single-wall carbon nanotubes and engineered multi-wall carbon nanotubes

Abstract: An extensive study on the optical characteristics of vertically aligned single-wall carbon nanotubes (SWCNTs) and engineered multi-wall carbon nanotubes (MWCNTs) using finite-difference time-domain (FDTD) simulation technique is presented in this work. We investigated absorption characteristics for SWCNTs, MWCNTs, dual-diameter MWCNTs, and cone MWCNTs with the changes in the occupation area and incident angle of light in the visible wavelength range. The enhancement of absorption was achieved by changing the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…This is mainly due to the higher thermal conductivity coefficient along the length direction when compared to the diameter direction [ 127 ]. Tahmid et al also demonstrated that the light absorbance is maximized when the direction of light incidence is equal to the length direction of the CNT, as shown in Figure 12 [ 132 ].…”
Section: Acoustic Wave Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly due to the higher thermal conductivity coefficient along the length direction when compared to the diameter direction [ 127 ]. Tahmid et al also demonstrated that the light absorbance is maximized when the direction of light incidence is equal to the length direction of the CNT, as shown in Figure 12 [ 132 ].…”
Section: Acoustic Wave Generationmentioning
confidence: 99%
“… CNTs’ average light absorbance (A avg ) as a function of the light incidence angle. Reproduced with permission from [ 132 ]. …”
Section: Figurementioning
confidence: 99%
“…The optimum condition is achieved for 1000-2000 nm variation, where maximum average absorbance (A avg ) is found for both 25% and 50% fillfactors as depicted in figure 4(d). Here, average absorbance is defined as [26]…”
Section: Randomness In Heightmentioning
confidence: 99%
“…[1][2][3][4][5][6] However, broadband absorbers are essential for photovoltaic cells, 7,8 photodetectors, 9 and thermal emitters. 10,11 Over the years, broadband photon absorbers with various structures such as nanowires, 12 nanopillars, 13 triangular and pyramid gratings, 14 nanocones, 15 plasmonic nanostructures, 16 and nanoholes 17 have been reported theoretically and experimentally for harvesting solar energy. Most of the reported research studies mainly focused on absorbing the visible light spectrum; however, approximately half of the sunlight that reaches the surface of the Earth contains infrared radiation.…”
Section: Introductionmentioning
confidence: 99%